Agency costs and the monetary transmission mechanism - Michael Reiter; Tommy Sveen; Lutz Weinke (Institute for Advanced Studies (IHS), 2017)
Once New Keynesian (NK) theory (see, e.g., Woodford 2003) is combined with a standard model of investment (see, e.g., Thomas 2002), the resulting framework loses its ability to generate a realistic monetary transmission mechanism. This is the puzzle uncovered in Reiter et al. (2013). The simple economic reason behind it is the unrealistically large interest rate elasticity of investment, as implied by standard investment theory. In order to address this puzzle we develop a NK model featuring fully flexible investment combined with a financial friction in the spirit of Carlstrom and Fuerst (1997). This model is used to isolate the quantitative importance of the financial friction for the monetary transmission mechanism.
Keywords: E22; E31; E32; 330; Financial Frictions; Sticky Prices